2020
DOI: 10.1017/s0007114520002822
|View full text |Cite
|
Sign up to set email alerts
|

Does polymorphisms in PPAR and APOE genes modify associations between fatty acid desaturase (FADS), n-3 long-chain PUFA and cardiometabolic markers in 8–11-year-old Danish children?

Abstract: n-3 long-chain polyunsaturated fatty acids (LCPUFA) can improve cardiometabolic blood markers but studies in children are limited. Single nucleotide polymorphisms (SNPs) in the FADS genes, which encode fatty acid desaturases, influence endogenous LCPUFA production. Moreover, SNPs in genes that encode peroxisome proliferator-activated receptors (PPAR) and apolipoprotein E (apoE) may modulate the effects of n-3 LCPUFA. We explored whether FADS polymorphisms were associated with blood cholesterol and triacylglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…This is in agreement with the results of previous research, where fish oil reduced plasma glucose only in carriers of the rs1801282 G allele in the PPRG2 gene ( 74 ). Damsgaard et al ( 73 ) found an inverse association between seric n -3 LCPUFA and triglycerides only in the PPARG2 rs1801282 G allele carriers, which concurs with the results of a previous study in infants ( 74 ). Blood n -3 LCPUFA was positively associated with LDL-c in children who were C allele homozygous of the rs1801282 SNP in the PPARG2 gene ( 73 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is in agreement with the results of previous research, where fish oil reduced plasma glucose only in carriers of the rs1801282 G allele in the PPRG2 gene ( 74 ). Damsgaard et al ( 73 ) found an inverse association between seric n -3 LCPUFA and triglycerides only in the PPARG2 rs1801282 G allele carriers, which concurs with the results of a previous study in infants ( 74 ). Blood n -3 LCPUFA was positively associated with LDL-c in children who were C allele homozygous of the rs1801282 SNP in the PPARG2 gene ( 73 ).…”
Section: Discussionsupporting
confidence: 87%
“…A recent study found that PPRAG rs1801282 modified the association between n -3 long-chain PUFA (LCPUFA) and serum insulin with an inverse association in minor allele (Ala12 = G) carriers only and no interaction between fatty acid desaturase FADS or n -3 LCPUFA and plasma glucose ( 73 ). This is in agreement with the results of previous research, where fish oil reduced plasma glucose only in carriers of the rs1801282 G allele in the PPRG2 gene ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle factors contribute to the high variation observed in glycemic responses among individuals as well as interactions between SNPs. Factors such as diet [54], weight loss [55], exercise [59], and fatty acid levels [60] have been documented to influence or interact with SNPs. Furthermore, gene-gene interactions should be taken into account when assessing the influence of SNPs in metabolic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Current research shows, n-3 PUFAs control the expression of a great variety of genes through different transcriptional factors, such as SREBP ( 169 ), PPARs ( 170 ), ChREBP ( 171 ), and NF-κB ( 172 ), which mainly regulate target gene transcription that encodes proteins involved in lipid and carbohydrate metabolism, thermogenesis, and inflammatory processes. However, it is important to point out that further studies are needed to elucidate these roles and to better understand the beneficial role of n-3 PUFAs in the mechanism of Cd exposure-induced disease, and to probe into their function as protective nutrients, aiming to prevent or treat the development of Cd exposure-related diseases.…”
Section: Discussion and Outlookmentioning
confidence: 99%